Control of a single-phase unity power factor rectifier - Nur Azhar Amin. (2011)
This report presents the implementations and control of a single-phase unity power factor rectifier. The implemented rectifier is a uni-directional boost rectifier. For the rectifier, adaptive controllers are employed to regulate the output voltage and to achieve unity power factor in the presence of uncertain loads. Experimental results are provided to show the effectiveness of these controllers in achieving unity power factor as well as output regulation.